ORGANIZATIONAL CULTURE AND JOB SATISFACTION AFFECT TEACHER PERFORMANCE AT KELING KUMANG SEKADAU VOCATIONAL SCHOOL - Adil Bertus; Fitria Elvi; Jonathan Giovanni (Jurnal Ekonomi, 2023)
Keling Kumang Vocational School is a vocational high school with the most students in Sekadau District. Of course, the success factor of the school is the teachers' performance and how the organizational culture is an important factor in improving teacher performance in carrying out every activity at school. Another thing that is no less important is teachers' job satisfaction as a driving force in doing work. Therefore the purpose of this research is to find out "The Influence of Organizational Culture and Job Satisfaction on the Performance of Keling Kumang Vocational School Teachers" The respondents of this study were all Keling Kumang Vocational School teachers using interview and questionnaire methods. Then the data was processed using SPSS. From the results of this study, it can be concluded that organizational culture significantly influences teacher performance with a Sig. 0.002 is smaller than 0.05, while job satisfaction has no significant effect on the Sig level. 0.05. But simultaneously, these two variables (organizational culture and job satisfaction) affect the performance of Keling Kumang Vocational High School teachers.